Teachers’ Challenges and Strategies in Developing Deep Learning-Oriented English Lesson Plans - Salsabila Abelagista Anindya; Elis Susanti (Universitas Islam Negeri Palopo, 2026)
This study aims to explore the challenges and strategies of English teachers in developing deep learning-oriented lesson plans under the Merdeka Curriculum in a vocational high school context. This research employed a qualitative case study design involving four English teachers selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that teachers generally possess a strong conceptual understanding of deep learning, emphasizing meaningful, contextual, and student-centered learning. However, a gap exists between teachers’ conceptual understanding and its practical implementation in lesson planning. The challenges identified include diverse student abilities, time constraints, curriculum demands, and limited resources. In addition, teachers’ prior teaching experiences influence both their strengths and difficulties in adapting to deep learning approaches. To address these challenges, teachers apply various strategies, such as implementing student-centered activities, adapting learning materials to vocational contexts, engaging in reflective practices, and integrating technology into lesson planning. These findings indicate that lesson planning is a complex cognitive process shaped by the interaction of teachers’ beliefs, knowledge, experiences, and contextual factors. This study highlights the need for continuous professional development and stronger institutional support to bridge the gap between conceptual understanding and practical implementation of deep learning in English language teaching, particularly in vocational education settings.